Factors Associated with Electricity Losses in Colombia - Briseño, Hugo; Rubiano, Jessica; GarcÃa, Rodolfo; Rojas, Omar (International Journal of Energy Economics and Policy, 2021)
The purpose of this research is to explore the factors associated with transmission and distribution electricity losses in Colombia. A literature review is carried out to find out the variables that have been significant in past studies. Once the issue is contextualized in the Colombian case, a statistical and econometric analysis is developed with the available variables. Transmission and distribution electricity losses were found to be positively significantly associated with crime, unemployment, and income; while these have a negative association with urbanization and population density. Results are of interest to practitioners, academics and policy makers. Keywords: Electricity Losses, Non-Technical Losses, T&D Losses, Power Losses, crime, econometric model. JEL Classifications: L94, N70, Q41 DOI: https://doi.org/10.32479/ijeep.11590